ANALISIS EFEKTIVITAS PENGENDALIAN BIAYA DAN PERPUTARAN MODAL KERJA TERHADAP RENTABILITAS PADA PT. PERKEBUNAN NUSANTARA IV (PERSERO) MEDAN - Tiur Rajagukguk; Debby Y. V. Silalahi; Hotlan Butarbutar (Majalah Ilmiah METHODA, 2022)
This study aims to analyze the Effectiveness of Cost Control and Working Capital Turnover on Profitability at PT. Perkebunan Nusantara IV (Persero) Medan for the 2017-2019 period. The financial ratios used in this study are Cost Control Effectiveness as measured by the ratio of Operational Costs and Operating Income (BOPO), Working Capital Turnover and Profitability as measured by Return on Assets (ROA). The method of data analysis is descriptive qualitative. The results of the study, with a decrease in the company's BOPO ratio during the 2017-2019 period every year, is a good indication, because it gives an illustration that this company can reduce its operational costs. When analyzed from a financial management aspect, under such conditions, it means The company's financial performance in terms of working capital turnover ratio is not good. This should be immediately corrected by the company by improving working capital management. The ROA ratio of PT. Perkebunan Nusantara IV (Persero) Medan compared to the standard ratio contained in table 2.1, the ratio of this company is at a standard of <10% with unfavorable criteria.